2004
DOI: 10.1002/ejic.200300898
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Structure and Catalytic Activity of Six‐Coordinate Chloro(hydrido)‐ and Dihydridoruthenium(II) and ‐osmium(II) Complexes with the Chiral Ligands PiPr2NH(Me)Ph, (S,S)‐Chiraphos and (S,S,)‐Diop

Abstract: The five-coordinate compounds [MHCl(CO) (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Treatment of (R)-α-methylbenzylamine with ClP i Pr in the presence of external base cleanly produced the desired phosphinoamine (R-PhCH 3 CH)NHP i Pr 2 (1) in 93% yield. The physical properties as well as the 1 H and 31 P NMR spectra of 1 exactly matched those reported in the literature for the opposite enantiomer [45].…”
Section: Chiral Phosphinoamide Ligandssupporting
confidence: 82%
“…Treatment of (R)-α-methylbenzylamine with ClP i Pr in the presence of external base cleanly produced the desired phosphinoamine (R-PhCH 3 CH)NHP i Pr 2 (1) in 93% yield. The physical properties as well as the 1 H and 31 P NMR spectra of 1 exactly matched those reported in the literature for the opposite enantiomer [45].…”
Section: Chiral Phosphinoamide Ligandssupporting
confidence: 82%
“…[3] Moreover, under a hydrogen atmosphere, complex 1 also catalyzes the reduction of cyclohexene, 1,3-and 1,4-cyclohexadiene, styrene and phenyl-and diphenylacetylene. [4,5] After we observed that the PiPr 3 ligands of 1 can easily be replaced by chiral mono-and bisphosphanes such as PiPr 2 NHCH(Me)Ph, (S,S)-Chiraphos and (S,S)-Diop, [6] we became interested to find out whether a similar substitution reaction would also occur with hemilabile, potentially chelating phosphanes. We note that the chemistry of a manifold of osmium and ruthenium compounds with phosphane ethers, phosphane esters and phosphaneamines as ligands has recently been investigated in our laboratory as well as by others.…”
Section: Introductionmentioning
confidence: 99%
“…Although ruthenium-phosphanes are well-known systems, they are still of interest. Studies on new ruthenium complexes [19] as well as mechanistic reports [20,21] other applications, for example in the development of sensors [22] or as a tool in supramolecular chemistry [23].…”
Section: Introductionmentioning
confidence: 99%